El asesinato de Cn. Calpurnio Pisón - Amela Valverde, Luis (Gerión. Revista de Historia Antigua, 2002)
In the present study is analyzed the murder of Cn. Calpurnius Piso, quaestor pro praetore of Citerior, by his cavalrymen in the year 64 d.C. The death is related to the Pompey's clientship in Spain and the delicater matter of «First Catilinarian Conspiracy». 1.